Service Quality Dimensions and Impact on Purchasing Decisions: A Case Study at Cuan Farma Pharmacy, Jakarta - Subagya, Guruh; Nur Tanty, Herty; Dwi, Meiana; Syafira, Syafira (Journal Syifa Sciences and Clinical Research, 2025)
In Indonesia’s increasingly competitive pharmacy market, driven by the growth of online platforms and large pharmacy chains, service quality has become a decisive factor in attracting and retaining customers. This study examined how the five SERVQUAL dimensions influence purchasing decisions at Cuan Farma Pharmacy in East Jakarta. A cross-sectional quantitative design was applied with 287 respondents selected through systematic random sampling. Service quality was measured using a validated and reliable questionnaire (Cronbach’s Alpha = 0.94) and analyzed with multiple linear regression. The results showed that tangibles, reliability, responsiveness, and empathy had significant positive effects on purchasing decisions (p 0.05), with empathy emerging as the strongest driver. Assurance, however, was not significant (p 0.05), suggesting that customers perceive it as a basic expectation rather than a differentiating factor. Together, service quality dimensions explained 47.2% of the variance in purchasing decisions, while the remainder was influenced by other factors such as price, location, and product availability. These findings underscore the importance of enhancing empathy and responsiveness, supported by reliability and tangible aspects, to strengthen customer loyalty and competitiveness in the pharmacy sector.